AOTX INDICES IN RESPONSE TO THE CROPS YIELD UNDER THE MALAYSIA CLIMATE - Mohammed, N. I. (2011)
Ground level ozone (O3) is an atmospheric pollutant that encompasses a phytotoxic gas, which has much potential to cause adverse impacts on plants in the agricultural regions. The purpose of this study was to look at the contributions of ozone to Accumulated exposure Over a Threshold of X ppb (AOTX) indices in response to the crops yield, under the Malaysia climate. Besides that, estimation of rice (Oryza sativa) reduction in Kedah, (‘rice bowl’ of Malaysia) due to ozone exposure was calculated based on the European benchmark. Environmental parameter that was used in this study was ozone concentration. These data were observed from 7a.m to 7p.m every day. However, the most critical AOTX index due to crops reduction that is suitable for Malaysia climate is still under investigation. According to the European benchmark, for AOT40 values above 3000 ppb, a 5% of yield loss is anticipated to occur. Based on the study, the value of AOT40 illustrates that the most of t he months in year 2004 had exceeded the European benchmark. Thus, approximately, 1.60 tonnes per hectare of paddy yield loss occurred in year 2004. This data concluded that the ozone exposure to crops will reduce the production of the paddy.